The Effects of International Trade on Structural Convergence and CO2 Emissions - Michael Hübler; Eduard Bukin; Yuting Xi (Environmental and Resource Economics, 2022)
This article introduces a new econometric model that includes an innovative measure of intersectoral structural change. This model describes the structural convergence (or divergence) of sector share patterns across countries (from the North-South or global perspective) influenced by international trade. The econometric analysis applies panel data estimators with different types of fixed effects to the 2013 and 2016 releases of the World Input-Output Database, covering the periods 1995–2009 and 2000–2014. The results show that international trade mostly~promotes structural convergence, which is enhanced by sectoral capital intensities. It seems, however, that in this millennium, structural divergence, also fostered by international trade, occurred in terms of the CO 2intensity of production.
Keywords: C51; F14; F18; O11; O44; 330; Structural change; International trade; CO2; Macro-econometrics; Panel data; WIOD